2013
DOI: 10.2174/1568026611313030005
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential (TRP) Channels and Cardiac Fibrosis

Abstract: Cardiac fibrosis is associated with most cardiac diseases. Fibrosis is an accumulation of excessive extracellular matrix proteins (ECM) synthesized by cardiac fibroblasts and myofibroblasts. Fibroblasts are the most prevalent cell type in the heart, comprising 75% of cardiac cells. Myofibroblasts are hardly present in healthy normal heart tissue, but appear abundantly in diseased hearts. Cardiac fibroblasts are activated by a variety of pathological stimuli, such as myocardial injury, oxidative stress, mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 172 publications
(224 reference statements)
1
63
0
1
Order By: Relevance
“…Extensive evidence has shown that there is a welldocumented association of Ca 2+ and cardiac fibrosis (6,27). Intervention and modulation of Ca 2+ channels and Ca…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive evidence has shown that there is a welldocumented association of Ca 2+ and cardiac fibrosis (6,27). Intervention and modulation of Ca 2+ channels and Ca…”
Section: Discussionmentioning
confidence: 99%
“…Although the expression of some TRP channels can be detected by using RT-PCR and appears to be associated with cardiac fibrosis, many of them cannot be detected by using electrophysiological recordings (6,30). Du and colleagues have found that silencing TRPM7 greatly diminishes the endogenous TRPM7 currents and Ca 2+ influx, which impairs the sensitivity of human atrial fibroblasts to TGF-b1-induced proliferation and differentiation.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Transient Receptor Potential Channels and Cardiac Fibrosis. Cardiac fibrosis is not a distinct entity; rather, it is a common pathologic pathway for various diseases (e.g., AMI and chronic ischemic heart disease, inflammatory and hypertrophic cardiomyopathies, and aging-associated heart disease) that damages the myocardium (reviewed in Yue et al, 2013). The damaged myocardium is then replaced by connective tissue synthesized by fibroblasts and myofibroblasts.…”
Section: Transient Receptor Potential Channels In Cardiovascular Dmentioning
confidence: 99%
“…By contrast, myofibroblasts are rare in the healthy heart but become enriched during disease. In response to pathogenic stimuli (e.g., myocardial injury, oxidative stress, and/or mechanical stretch), fibroblasts get activated and a subset differentiates into myofibroblasts (see Yue et al, 2013). In turn, activated fibroblasts and myofibroblasts excessively synthesize and deposit extracellular matrix proteins.…”
Section: Transient Receptor Potential Channels In Cardiovascular Dmentioning
confidence: 99%